Nothing is Sacred...Or a Dispassionate Look at Government Deficits - Vinhas da Silva, Rui; Natália Teixeira (SSRN, 2014)
Abstract: A few years ago Robert Barro published a book, aptly called “Nothing is Sacred” (2003). In it he dealt with an area of intellectual query in economic sciences that has always attracted the interest and opinion of many. In effect there has been much controversy and contention over the critical importance of keeping a tight fist on government spending, and conversely on whether compliance by national economies with public debt/GDP ratios (around 60%) is attainable by way of an emphatic focus on the numerator of this ratio. In this paper we argue that the imperative of keeping budget deficits tightly under control should not undermine the policy measures that are needed for augmenting the denominator in the same ratio, in other words economic growth (Cecchetti et al., 2010). Given the truly alarming public debt situation afflicting not only Eurozone economies, but also global economic powerhouses, there have been more and more calls for government policy measures aimed at the curtailment of public spending and the reduction of public sector deficits (Buti, et al., 2003). The poignant question remains however, as to whether under current conditions, these economies can ever escape the stranglehold of severe austerity in which they are deeply submerged.